Concepts and techniques to improve resin/resin bonding. Literature Review. (International Journal of Medical and Surgical Sciences, 2019)
The availability of new scientific information about the etiology, diagnosis and treatment of carious lesions and the introduction of reliable adhesive restorative materials substantially reduced the need of extensive tooth preparations. In order to achieve a successful procedure, an adequate bonding interface between old and new composite is required. The aim of this article is to review the concepts and techniques described in the literature for the improvement of resin-resin bonding. Bonding to dentin has been quite difficult to achieve. The difficulties are that dentin’s histological structure and chemical composition are very different from those of the enamel. Bonding to dentin requires, besides acid conditioning and the adhesive required for enamel, a primer or dentin bonding agent, which is a hydrophilic, able to penetrate by infiltrating the microscopic spaces of the collagen mesh. The repairing of faulty restorations is a treatment option that has proven to be quite effective and safe, since it presents excellent results over time. For this purpose, different methods for surface treatment have been developed, which has a great effect on the resistance of the reparation bonding. In order to achieve successful bonding between both resins, the following steps are recommended, including: surface roughening, acid etching, silane application, and bonding agent application.
Keywords: adhesion; resin; bonding; dentin